GEOMETRICAL EFFICIENCY OF PLANE-PARALLEL IONIZATION CHAMBERS IN PROTON SCANNING BEAM. Issue 1 (11th October 2017) - Mojżeszek, N; Kłodowska, M; Komenda, W; Stolarczyk, L; Kopeć, R; Olko, P
Abstract: For commissioning of a proton therapy unit depth dose distributions must be determined and introduced into the Treatment Planning System. In pencil beam scanning (PBS) technique, integral depth dose (IDD) acquisition should be performed with detector large enough to ensure entire beam laterally broadened by scattered and secondary contributions. The purpose of this article is to quantify, using measurements and Monte Carlo transport calculations, the ionization chamber's (IC) geometrical efficiency versus the chamber radius and proton beam energy. The geometrical efficiency of 0.99 was determined for energies up to 160 and 190 MeV for 4.08 and 6 cm radius IC. Much lower geometrical efficiency was obtained for the energy of 226.08 MeV and results in charge loss of 5.8 and 3.6%, respectively. Relative IDD differences between IC 4.08 and 6 cm in radius increase with proton energy and reach 2.4% at the mid-range depth for 226.08 MeV.